The combined use of vitamin B1 and vitamin B12 accelerates the recovery of gastrointestinal function after rectal cancer surgery - Tang, Song; Luo, Simin; Fang, Weikun; Chen, Zhenyu; Liao, Yongfang; Cai, Huiqiang; Zhang, Weibin; Chen, Dan (Frontiers in Nutrition, 2025)
BackgroundThe recovery of gastrointestinal function after rectal cancer surgery is a key factor influencing patients’ postoperative quality of life. This study is the first to explore the role of vitamin B1 and B12 in the recovery of gastrointestinal function after rectal cancer surgery.MethodsEligible patients were divided into four groups: no vitamin group, vitamin B1 alone group, vitamin B12 alone group, and combined vitamin B1 and B12 group. Univariate analysis was used to compare the differences in the time to first flatus among the four groups. Due to the small number of patients using only vitamin B1 or only vitamin B12, these patients were excluded, and univariate and multivariate linear regression analyses were performed on the time to first flatus.ResultsThe time to first flatus exhibited a non-normal distribution. The Kruskal-Wallis rank sum test indicated significant differences in the time to first flatus among the four groups (p = 0.0152). However, Dunn’s pairwise comparison test showed that only the combined vitamin B1 and B12 group differed significantly from the no vitamin group (p = 0.001). Univariate linear regression analysis demonstrated that intraoperative blood loss (p = 0.001), enterostomy (p = 0.002), ileostomy (p < 0.001), and combined use of vitamin B1 and B12 (p = 0.007) significantly affected the time to first flatus. After removing variable with severe multicollinearity, the results of the multivariate regression analysis showed that intraoperative blood loss (p = 0.001), ileostomy (p = 0.001), and combined use of vitamin B1 and B12 (p = 0.026) still had significant effects on the time to first flatus.ConclusionThe combined use of vitamin B1 and B12 can accelerate the recovery of gastrointestinal function after rectal cancer surgery.